Generation of an induced pluripotent stem cell (iPSC) line from a 40-year-old patient with the A8344G mutation of mitochondrial DNA and MERRF (myoclonic epilepsy with ragged red fibers) syndrome - Yu-Ting Wu; Yu-Hung Hsu; Ching-Ying Huang; Ming-Ching Ho; Yu-Che Cheng; Cheng-Hao Wen; Hui-Wen Ko; Huai-En Lu; Yen-Chun Chen; Chia-Ling Tsai; Yi-Chao Hsu; Yau-Huei Wei; et al. (Stem Cell Research, 2018)
Mitochondrial defects are associated with clinical manifestations from common diseases to rare genetic disorders. Myoclonus epilepsy associated with ragged-red fibers (MERRF) syndrome results from an A to G transition at nucleotide position 8344 in the tRNALys gene of mitochondrial DNA (mtDNA) and is characterized by myoclonus, myopathy and severe neurological symptoms. In this study, Sendai reprogramming method was used to generate an iPS cell line carrying the A8344G mutation of mtDNA from a MERRF patient. This patient-specific iPSC line expressed pluripotent stem cell markers, possessed normal karyotype, and displayed the capability to differentiate into mature cells in three germ layers.